Sign and Symptom of Temporomandibular Joint Disorders and Associated Parafuncion Habits in Young Adults - Wajiha Malik, Sadaf Malik, Sheema Shakir, Asifullah Khan, Amra Qadeer, Waqar Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to determine the signs and symptoms of temporomandibular joint diseases and parafunctional habits contributing to TMD. Method: Using a structured proforma and questionnaire data was collected from 162 subjects to determine signs and symptoms of temporomandibular joint diseases and associated parafunctional habits contributing to TMD. Results: The results showed that most frequent reporting sign was painful TMJ(61.4% females)and (56.96% males)while least frequent sign was deviation of mandibular movement representing(24.09% and 26.58%) neck stiffness(26.0%and 22.7%)and mandibular deviation(24.09%and 26.58%).clicking and clenching was reported to be 49.39% and 42.16% in females and 39.24%and 40.50% in males respectively. The percentage distribution of headache was noted to be 42.16% in females and 40.50% in males. while 60.24% females and 44.30% males reported themselves to be stressed or tense. Painful muscles were however reported by 33.73% females and 27.84% males. Lip and cheek biting /chewing gums was the most common parafunctional habit(41.97%)with females significantly more than males, followed by nail biting and bruxism(15.43% and 14.19%).Thumb sucking was found to be present in 4.9% of individuals. However 23.45% reported themselves to be free of any habit. Conclusion: The study has shown that TMD remains largely undiagnosed in our general population and it can be related very well with anxiety, headache and bad lifestyle habits.